Cobalt based new quaternary Heusler alloys for Spintronic and thermoelectric applications: an Ab-initio study. (19th September 2022) - Priyanka, D. Shobana; Sudharsan, J. B.; Srinivasan, M.; Ramasamy, P.
ABSTRACT: In this paper, we employed Density Functional Theory (DFT) to study structural and mechanical stability, electric, magnetic and electronic properties of cubic Co-based new quaternary half-Heusler alloys CoZrCrZ (Z = Al, Ga, In) using WIEN2k. Volume optimisation suggests that these alloys are stable in the Y1 structure and show ferromagnetic behavioTAur. Generalised Gradient approximation calculations confirm the half-metallic nature of the reported alloys, which show metallic nature, and semiconducting band gaps exist in spin-up and spin-down channels, respectively. From the calculated cubic elastic constants, the reported Heusler alloys shows ductile nature. The calculated spin-magnetic moments of CoZrCrZ (Z = Al, Ga, In) are consistent with the Slater-Pauling rule. The very fine narrow band gap in the spin-down channel enhances the thermoelectric properties. The reported ferromagnetic half-metals with good thermoelectric parameters suggests that these alloys have possible applications in spin-based electronics and green energy technology.